A historical perspective of how public policy shaped dialysis care delivery in the United States. Issue 1 (14th January 2020) - Anumudu, Samaya J.; Eknoyan, Garabed
Abstract: Broadly defined public policy has been said to be whatever "governments choose to do or not to do" As applied to healthcare, public policy can be traced back to the 4000‐year‐old Code of Hammurabi. As it applies to dialysis care its history is barely 50 years old since national coverage for end‐stage renal disease (ESRD) was legislated as Public Law 92‐603 in 1972. As with most healthcare policy changes, it was a result of medical progress which had changed renal function replacement by dialysis from its rudimentary beginnings during the Second World War into an experimental acute life‐saving procedure in the 1950s and to an established life‐sustaining treatment for the otherwise fatal disease of uremia in the 1960s that was limited by its costs. Since 1973, the Medicare ESRD Program has saved the lives of thousands of individuals, a compassionate achievement that has come at increasing costs which have exceeded all estimates and evaded containment. Apart from cost containment, policy changes in dialysis care have been directed at improving its safety and adequacy. Some of the results of these changes are evident as one compares the outcomes and complications of dialysis encountered in the 1970s to those in the present; others, particularly those related to vascular access and hospitalization rates have improved modestly. This article recounts the historical background in which national coverage for dialysis care was developed, legislated and has evolved over the past 50 years.